2019
DOI: 10.26434/chemrxiv.10043138
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small Molecule NF-kB Inhibitors as Immune Potentiators for Enhancement of Vaccine Adjuvants

Abstract: <p>Adjuvants are added to vaccines to enhance the immune response and provide increased protection against disease. In the last decade, hundreds of synthetic immune adjuvants have been created, but many induce undesirable levels of proinflammatory cytokines including TNF-a and IL-6. Here we present small molecule NF-kB inhibitors that can be used in combination with an immune adjuvant to both decrease markers associated with poor tolerability and improve the protective response of vaccination. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…18 Although these adjuvants can be potent activators of immune responses, a well-known limitation of current popular adjuvants is excessive and uncontrolled inammation. 1,11,19 This has motivated efforts to discover novel adjuvants with reduced inammation proles, 20,21 but it has proved challenging to develop novel PRR agonists capable of specically tuning the level of stimulation in inammatory pathways without disrupting the desired stimulation along immune activation pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Although these adjuvants can be potent activators of immune responses, a well-known limitation of current popular adjuvants is excessive and uncontrolled inammation. 1,11,19 This has motivated efforts to discover novel adjuvants with reduced inammation proles, 20,21 but it has proved challenging to develop novel PRR agonists capable of specically tuning the level of stimulation in inammatory pathways without disrupting the desired stimulation along immune activation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…20 As compared to peptides like SN50, small molecules present attractive candidates for immunomodulators due to their better synthetic accessibility and reduced potential for immunogenicity. To this end, Moser et al 21 also demonstrated that a small molecule NF-kB inhibitor honokiol and its derivatives can be used as immunomodulators with similar functions to SN50. More recently, we conducted a targeted experimental screen of a small molecule library of ∼3000 compounds, many of which were known to inuence the immune system, to discover, aer removing cytotoxic compounds using the same viability lter as applied in the present study, novel molecules capable of suppressing NF-kB activity by up to 9-fold, elevating NF-kB activity by up to 7-fold and elevating IRF activity by up to 7-fold.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although these adjuvants can be potent activators of immune responses, a well-known limitation of current popular adjuvants is excessive and uncontrolled inflammation. 1,11,19 This has motivated efforts to discover novel adjuvants with reduced inflammation profiles, 20,21 but it has proved challenging to develop novel PRR agonists capable of specifically tuning the level of stimulation in inflammatory pathways without disrupting the desired stimulation along immune activation pathways.…”
Section: Introductionmentioning
confidence: 99%
“…20 As compared to peptides like SN50, small molecules present attractive candidates for immunomodulators due to their better synthetic accessibility and reduced potential for immunogenicity. To this end, Moser et al 21 also demonstrated that a small molecule NF-κB inhibitor honokiol and its derivatives can be used as immunomodulators with similar functions to SN50. More recently, we conducted a targeted experimental screen of a small molecule library of ∼3000 compounds, many of which were known to influence the immune system, to discover, after removing cytotoxic compounds using the same viability filter as applied in this study, novel molecules capable of suppressing NF-κB activity by up to 9-fold, elevating NF-κB activity by up to 7-fold and elevating IRF activity by up to 7-fold.…”
Section: Introductionmentioning
confidence: 99%